Differentiated protection strategy with dynamic traffic grooming based on clustering - Yu XIONG; Yuan-yuan LI; Jian-bo TANG; Ying ZHAO; Ru-yan WANG (Tongxin xuebao)
To make dynamic traffic grooming faster and more efficient,and achieve an intelligent differentiated protection,a differentiated protection strategy with dynamic traffic grooming based on clustering(DPS-DTGC)was proposed.The whole network topology was allocated some clusters based on maximal independent set,in order to reduce the routing time consumption.Meanwhile,by the cooperation of layered auxiliary graph,residual capacity matrix and cluster aggregation layer,the traffic in inter- and intra- clusters would been groomed to realize the reasonable planning of resources and the higher efficiency of grooming.Furthermore,according to the proportion of different priority traffic in one wavelength ,the link importance was evaluated and a smart P-cycle was designed to give differentiated protection to the link.The simulation results show this strategy can make a better utilization of network resource.And with the increase of network load,it will gain a good performance in blocking rate.